Analisis Pengembangan Desa Wisata Berbasis Penta Helix di Desa Jambu Kabupaten Kediri: (Studi pada Desa Wisata Jambu Kabupaten Kediri) - Resti Oktaviarni (Jurnal Ilmiah Administrasi Publik, 2023)
The research aims to describe the role of Penta Helix model actors in the development of Agro Petik Kelengkeng, Jambu Tourism Village, Kediri Regency and to describe the supporting and inhibiting factors of the role of Penta Helix model actors in the development of Agro Petik Kelengkeng, Jambu Tourism Village, Kediri Regency. Type of this research is a descriptive and qualitative approach. Data collection techniques are interviews, observations, and documentations. Data analysis used interactive analysis models from Miles, Huberman, and Saldana (2014). The results of the study only four actors in the form of academic, community, media and government played a role in the development of Agro Petik Kelengkeng. The conclusion obtained in the form of Penta Helix actors did not run optimally because there was no role of business actors. Research suggestions are conducting CSR programs, Non-governmental organizations (NGOs) can be involved in the development of Jambu Tourism Village, forming publication media teams, and involvement of Government actors to conduct social media publication training.